Obtenção da população base para um programa de seleção recorrente em Brachiaria humidicola - Berchembrock, Yasmin Vasques (2017)
The Brachiaria humidicola is an important forage specie, due to its adaptation to acidic and poorly drained soils. However, when it comes to genetic improvement, such specie presents a strong limitation regarding the existence of a single polyploid sexual source. The objective of this study was to select superior sexual hybrids with agronomic and nutritional value traits, based on the evaluation of B. humidicola half-siblings progenies, from the first cycle of intrapopulational recurrent selection. In addition, genetic parameters were estimated in order to help in the definition of selection strategies reporting on the possibility of genetic gains. In the outline of incomplete blocks, nine half-siblings progenies of the cross-breeding between sexual parents were evaluated, making 605 hybrids. The agronomic characteristics of green field weight ( GFW), percentage of leaf (% L), leaf:steam ratio (LSR), total dry matter yield (TDMY), leaf dry matter yield (LDMY) and regrowth (REG) in up to six cuts performed at intervals of 30 to 60 days in the rainy season and dry season. The nutritive value traits were evaluated in crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), in vitro digestibility of organic matter (IVDOM) and lignin (LIG) evaluated in two cuts. It was observed the absence of variability of the total additive effects, however, when considering permanent effects of individuals significant differences were observed (p <0.05) for most of the evaluated characters, indicating the predominance of dominance effects in the genetic control of these characteristics. The genetic correlations were positive among agronomic characters, with emphasis on GFW, which presented higher magnitude of correlation with TDMY and LDMY. The characters of nutritive value presented lower to negative magnitudes of correlations with agronomic characters, indicating difficulty in the association of these characteristics with the selection. The direct gains estimated from the selection were positive for all the characteristics, besides showing a good coincidence with the gains based on the multi-characteristic selection, indicating possibility of selection of superior genotypes of B. humidicola and progress with the selection in cycles of recurrent intrapopulation selection.